2000
DOI: 10.1034/j.1399-3046.2000.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Allograft with unrelated donor accentuates the gastrointestinal toxicity associated with high‐dose melphalan and total body irradiation preparative for bone marrow transplantation in children

Abstract: The use of high-dose melphalan (L-phenyalalanine mustard or L-PAM) has been shown to be associated with both hematological and non-hematological toxicity. It has been employed in the conditioning for allogeneic stem cell transplants from related donors but experience on its use in the unrelated setting has not been reported. As an attempt to elucidate the role of high-dose L-PAM (210 mg/m2) and total body irradiation (TBI) as a preparative regimen for allogeneic marrow transplantation from matched unrelated do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The use of melphalan with TBI in particular appears to be associated with an increased risk of toxic complications. 11 Furthermore, the use of only serology in HLA typing for class I antigens runs the risk of one of the two groups being less polymorphic than the other. The possible effect of this cannot be evaluated in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The use of melphalan with TBI in particular appears to be associated with an increased risk of toxic complications. 11 Furthermore, the use of only serology in HLA typing for class I antigens runs the risk of one of the two groups being less polymorphic than the other. The possible effect of this cannot be evaluated in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This reason is that all patients in our study received transplantation from HLAidentical related donors. As Vettenranta et al (16) reported, allograft from an unrelated donor might accentuate the gastrointestinal toxicity associated with MEL and TBI. Various studies have found that the DFS after HLA-identical related donor transplantation in children with acute leukemia in CR1 or CR2 ranges from 30% to 70% (17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 94%
“…As Vettenranta et al. (16) reported, allograft from an unrelated donor might accentuate the gastrointestinal toxicity associated with MEL and TBI.…”
Section: Discussionmentioning
confidence: 95%